Return to sports after athletes undergo meniscal surgery: A systematic review - Lee, Y. S.; Lee, O.-S.; Lee, S. H. (Clinical Journal of Sport Medicine, 2019)
Objective: The aim of this systematic review was to determine the time to and rate of the return to sports (RTS) after meniscal surgery and to compare these values among the different types of meniscal surgeries.